Analysis of Speech Acts in Digital Interaction: A Pragmatic Study on the Instagram Platform Among Teens - Ghina Fauziyyah (Sekolah Tinggi Agama Islam Kuningan, 2025)
Digital interaction among teenagers through platforms such as Instagram has created unique new communication patterns, including in diverse and dynamic speech acts. The background of this research is to understand how digital context affects the variation of adolescents' speech behavior, both in terms of form, function, meaning, and social interaction patterns. This study aims to analyze the variation of adolescents' speech on Instagram and its impact in shaping social identity and strengthening relationships between them. The research method used is a qualitative approach, with data collection techniques in the form of participatory observation and in-depth interviews with active adolescent Instagram users. The data was analyzed through content analysis methods and thematic coding, which involved open coding, axial coding, and selective coding to identify key patterns and themes. The results of the study show that speech on Instagram is dominated by expressive forms, with the main function of sharing information, providing entertainment, and showing solidarity. The meaning of speech is often implicit, influenced by the context of social relationships and conversational situations. Interaction patterns such as question-and-answer, feedback comments, and jokes show the emotional closeness between users. In conclusion, the digital context provides flexibility for adolescents to express themselves and form strong social bonds, making social media a space that supports diversity of expression. These findings have implications for a better understanding of the dynamics of adolescent communication in the digital era.